From Open Legal Policy to Judicial Reversal: Constitutional Compliance and the Abolition of the Presidential Threshold in Indonesia - Ridwan Syaidi Tarigan; Husni Thamrin (Law Development Journal, 2026)
The presidential threshold regulation in Indonesia, as stipulated in Article 222 of Law Number 7 of 2017 on General Elections, has generated sustained constitutional controversy regarding its compatibility with fundamental democratic principles. This study critically examines the constitutional validity of the presidential threshold requirement, which mandates that political parties or coalitions secure a minimum of twenty percent of seats in the House of Representatives or twenty-five percent of the national vote to nominate presidential and vice-presidential candidates. Employing a normative juridical methodology that integrates statutory, conceptual, and case-based analytical approaches, this study investigates whether the threshold aligns with the constitutional guarantees of popular sovereignty, political equality, and protection of political rights enshrined in the 1945 Constitution of the Republic of Indonesia. The findings reveal that while the Constitutional Court has historically upheld the threshold on the basis of legislative discretion and governmental stability concerns, the provision generates structural tensions with democratic inclusivity and political pluralism. The landmark Decision Number 62/PUU-XXII/2024, in which the Court ultimately abolished the threshold, marks a significant judicial reorientation toward representativeness over governability. This study concludes that meaningful electoral reform must reconcile the imperatives of political stability with broader constitutional commitments to equal political participation, and recommends the introduction of alternative candidacy frameworks that are constitutionally grounded and democratically inclusive.